Notes on a Further Excavation of Ancient Dwellings at Skara, in the Parish of Sandwick, Orkney, made during August 1913: With Notes on the Remains found - Stewart, W Balfour; Dawkins, W Boyd (Proceedings of the Society of Antiquaries of Scotland, 1914)
Excavation revealed a complex of stone built chambers linked by passageways, one of which was roofed. A number of hearths were identified. Finds included pottery, limpet shells, red deer, ox and whale bone, an incised stone ball and stone mace-heads. The presence of a twig rune on a loose stone is evidence of later activity.